Oral history interview with Robert L. Price, November 1, 1999 - Price, Robert L. (Valdosta State University Archives and Special Collections, 1999)
Oral history interview with Robert L. Price, November 1, 1999. Valdosta (Ga.). Fieldworker: Latasha N. McCoy. Audio file. Part of the South Georgia Folklife Project at Valdosta State University Archives and Special Collections. Note: Poor audio quality.
1 electronic record(s) and derivatives. XXX audio file (wav, mp3) 545760906 bytes. 00:22:10. 3 PDF documents (3 scans, jp2). 1 digital photograph. 582 MB (610,933,400 bytes).
Keywords: Georgia; Sound recordings; Cairo (Ga.); African Americans; Priests; Gospel music